Do Analysts and Investors Fully Understand the Persistence of the Items Excluded from Street Earnings? - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2010)
Previous research has found that the items that are included in GAAP earnings but excluded from Street earnings to allow the firm to meet or beat analyst earnings forecasts (“MBF exclusions”) are more persistent than the other excluded items. In this study, I find that the difference in the levels of persistence between MBF and non-MBF exclusions declined after the introduction of Regulation G, which requires public companies that disclose non-GAAP earnings to also present GAAP earnings and a reconciliation of the two. Analysts underestimate the persistence of non-MBF exclusions, but the degree of this underestimation is lower in the post-regulation period. In contrast, there is little evidence to indicate that analysts underestimate the persistence of MBF exclusions in either time period. I also find strong (weak) evidence that investors underestimate the persistence of Street exclusions in the pre- (post-) regulation period. These results suggest that Regulation G constrains the practice of excluding recurring expenses from Street earnings to meet or beat analyst forecasts and helps analysts and investors to understand the persistence of Street exclusions.